IMPROVING PATTERN CLASSIFICATION THROUGH BEADING ACTIVITIES TO DEVELOP COGNITIVE SKILLS OF CHILDREN AGED 5–6 YEARS - Nurazizah, Siti; Purwani, Anisa (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
Cognitive development in early childhood is an essential aspect related to logical thinking skills, one of which can be fostered through pattern classification activities. Children’s cognitive abilities can be enhanced through interactive learning activities and the use of concrete media. This classroom action research aimed to improve pattern classification skills through beading activities for children aged 5–6 years at TK Pembina Liunggunung. The study was conducted using the Kemmis and McTaggart spiral model, which consists of planning, action, observation, and reflection stages, carried out in two cycles with two meetings in each cycle. The research subjects were 10 children from group B. Data were collected through observation, documentation, and field notes. The success indicator was determined if at least 80% of the children demonstrated an improvement in pattern classification skills. The findings showed a significant improvement: in cycle I the average achievement of indicators reached only 50%, while in cycle II it increased to 87.5%. This aligns with Sujiono’s (2012) opinion that fine motor-based activities such as beading can stimulate children’s logical thinking development through activities of comparing, sequencing, and classifying objects. Thus, it can be concluded that beading activities are effective in improving pattern classification skills and contribute to the cognitive development of children aged 5–6 years.